2020
DOI: 10.32890/mmj.8.1.2004.8752
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Poverty in Malaysia: Applications of Distributive-Sensitive Poverty Indices

Abstract: This paper represents an attempt to seek a better way to measure poverty in Malaysia. Many studies, including government published figures employ the head-count ratio as the index of poverty. However; this measure is a narrow measure of poverty. Specifically, it ignores the distribution of income among the poor, and hence has its limitation. Here, besides the usual simple head-count ratio (H) that was reported in most previous studies as well as in government documents, better poverty measures were employed— t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In his study applying distributive-sensitive poverty indices, Roslan (2004) concluded that all measurements used such as poverty-income gap index, Sen index, and FGT (Foster-Greer-Thorbecke) index, showed that there is evidence of poverty reduction, consistent with the government published figures. Employing Malaysian Family Life Survey (MFLS), Roslan (2004) used the cash and non-cash income to proxy income received by households. More recent studies by Mohd Taib (2002) andMohd Fauzi (2009) used social exclusion approach to study various patterns and behaviour of the poor.…”
Section: Resultsmentioning
confidence: 56%
“…In his study applying distributive-sensitive poverty indices, Roslan (2004) concluded that all measurements used such as poverty-income gap index, Sen index, and FGT (Foster-Greer-Thorbecke) index, showed that there is evidence of poverty reduction, consistent with the government published figures. Employing Malaysian Family Life Survey (MFLS), Roslan (2004) used the cash and non-cash income to proxy income received by households. More recent studies by Mohd Taib (2002) andMohd Fauzi (2009) used social exclusion approach to study various patterns and behaviour of the poor.…”
Section: Resultsmentioning
confidence: 56%
“…Accessibility to education has been associated with prevention of poverty and well-being (McNamara et al, 2017). This is because raising the well-being of the poor and the elimination of poverty will obviously enable the poor to realise their potential in society (Roslan, 2004). Despite the inherent value of education to the poor, there still seems to be an increasing number of out-of-school children in many developing countries.…”
Section: Literature Reviewmentioning
confidence: 99%